Bushfire Smoke in Our Eyes: Community Perceptions and Responses to an Intense Smoke Event in Canberra, Australia - Williamson, Rebecca; Banwell, Cathy; Calear, Alison L.; LaBond, Christine; Leach, Liana S.; Olsen, Anna; Walsh, Erin I.; Zulfiqar, Tehzeeb; Sutherland, Stewart; Phillips, Christine (Frontiers in Public Health, 2022)
The 2019-20 bushfires that raged in eastern Australia were an overwhelming natural disaster leading to lives lost and upended, and communities destroyed. For almost a month, Canberra, Australia’s capital city, was obscured by smoke from surrounding fires which threatened the outer suburbs. While smoke itself is experientially different from other natural disasters, it nevertheless poses a significant public health threat. We responded rapidly by conducting semi-structured interviews with a range of Canberra residents potentially vulnerable due to their personal or social circumstances to the effects of the smoke. Three major themes emerged from the interviews - narratives around disruption to daily life, physical and psychological effects, and changing social connectedness. This study explores the ambiguous but impactful nature of a bushfire smoke event, and we identify four simple key messages that we believe to be critically relevant to policy making in preparation for similar smoke events in the future.